Clinical Manifestation of Acute Myocardial Infarction in the Elderly (Medical Journal of Indonesia, 2003)
A retrospective study were performed in patients with acute myocardial infarction (AMI) that hospitalized in ICCU Cipto Mangunkusumo hospital, Jakarta during the period of January 1994 until Decmber 1999. There were 513 patients hospitalized with MCI, 227 patients (44.2%) were classified as elderly, and 35.2% of them were female. Most of the elderly AMI patients reported typical chest pain just like their younger counterparts. Elderly AMI patients tend to come later to the hospital, and more Q-wave myocardial infarction were identified compared to non- Q-wave myocardial infarction. Risk factors of diabetes mellitus and hypertension were more common among the elderly. The prevalence of atrial fibrillation and the mortality rate were higher among elderly AMI patients. (Med J Indones 2003; 12: 229-35)